2014
DOI: 10.1139/bcb-2014-0044
|View full text |Cite
|
Sign up to set email alerts
|

A novel role of transient receptor potential mucolipin1 (TRPML1) in protecting against imidazole-induced cytotoxicity

Abstract: Lysosomotropic amines cause serious side effects such as cytoplasmic vacuolation and cell death. TRPML1 (also known as mucolipin1), a member of the transient receptor potential (TRP) protein family, may regulate fusion/fission of vesicles along the endocytic pathway and some aspects of lysosomal ion homeostasis. Nevertheless, it is still unknown whether TRPML1 is involved in death of mammalian cells induced by lysosomotropic agents. In this study, imidazole was used as a model to investigate the role of TRPML1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…TRPML-1 plays a role in the control of cell viability and in chaperone-mediated autophagy [16]. It is involved in death of mammalian cells induced by lysosomotropic agents [26]. TRPML-1 is considered a reactive oxygen species (ROS) sensor localized on the lysosomal membrane that orchestrates an autophagy-dependent negative-feedback program to mitigate oxidative cell stress [27].…”
Section: Introductionmentioning
confidence: 99%
“…TRPML-1 plays a role in the control of cell viability and in chaperone-mediated autophagy [16]. It is involved in death of mammalian cells induced by lysosomotropic agents [26]. TRPML-1 is considered a reactive oxygen species (ROS) sensor localized on the lysosomal membrane that orchestrates an autophagy-dependent negative-feedback program to mitigate oxidative cell stress [27].…”
Section: Introductionmentioning
confidence: 99%
“…Our research was the precedent experiment which systematically studied the role of STK32C in promoting the proliferation in PDAC. Liu et al's study found that overexpression of MCOLN1 inhibited imidazole-induced vacuole formation and cell death in human endometrial adenocarcinoma (HEC-1B) cells [16]. In contrast, knockdown MCOLN1 increased the cell death induced by imidazole [16].…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al's study found that overexpression of MCOLN1 inhibited imidazole-induced vacuole formation and cell death in human endometrial adenocarcinoma (HEC-1B) cells [16]. In contrast, knockdown MCOLN1 increased the cell death induced by imidazole [16]. Moreover, a report in 2019 demonstrated that MCOLN1 inhibition could attenuate HRAS nanoclustering and plasma membrane abundance, ERK phosphorylation, and cell proliferation [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In human endometrial adenocarcinoma (HEC-1B) cells, TRPML1 overexpression inhibits vacuole formation and cell death induced by the lysosomotropic agent imidazole. In contrast, TRPML1 knockdown increases cell death induced by the same treatment (10). Thus, it was supposed that TRPML1 is able to protect against this kind of drug by regulating the pH of acidic organelles.…”
Section: Trpml1 and Cancermentioning
confidence: 99%